2019
DOI: 10.1111/bor.12373
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation and climate during the penultimate interglacial of the northeastern Russian Arctic: the Lake El'gygytgyn pollen record

Abstract: We present a high‐resolution reconstruction of the vegetation and climate dynamics during the penultimate interglacial, corresponding with Marine Isotope Stage (MIS) 7, based on detailed palynological analyses of lacustrine sediments from Lake El'gygytgyn, northeastern Siberia. The analysed sediments were deposited between 246 and 181 ka ago (late MIS 8 to early MIS 6.6). The interglacial vegetation was characterized by herb and shrub (mainly alder and birch) dominated plant communities. Pollen‐based biome rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Pollen assemblages of PZ III in section 118 (Figure 3) are dominated by Betula, Alnus and Pinus. In the El'gygytgyn pollen record (e.g., Lozhkin et al, 2007Lozhkin et al, , 2017Matrosova, 2009;Andreev et al, 2014;Zhao et al, 2018Zhao et al, , 2019, similar pollen assemblages have only been reported from the Late Pleistocene. During PZ III of section 118, larch forests with stone pines, shrub alders, dwarf birches, and ericaceous low shrubs in underbrush dominated the vegetation cover.…”
Section: Upper Pleistocenementioning
confidence: 83%
“…Pollen assemblages of PZ III in section 118 (Figure 3) are dominated by Betula, Alnus and Pinus. In the El'gygytgyn pollen record (e.g., Lozhkin et al, 2007Lozhkin et al, , 2017Matrosova, 2009;Andreev et al, 2014;Zhao et al, 2018Zhao et al, , 2019, similar pollen assemblages have only been reported from the Late Pleistocene. During PZ III of section 118, larch forests with stone pines, shrub alders, dwarf birches, and ericaceous low shrubs in underbrush dominated the vegetation cover.…”
Section: Upper Pleistocenementioning
confidence: 83%
“…; Zhao et al . ). The upper sandy layer (9.6–9.1 m) is probably associated with a transgression that occurred during the Allerød warming.…”
Section: Late Quaternary Lake‐level Changes: State Of the Artmentioning
confidence: 97%
“…The proportion of coniferous trees and warm-and-humid broadleaved trees from core DJH-2 was also compared with the trees and shrubs of the pollen record in Lake El'gygytgyn [50][51][52] (Figure 5). In Lake El'gygytgyn, the proportion of trees and shrubs also increased during MIS 7, MIS 5, and MIS 1.…”
Section: Regional Vegetation Contrasted Between Different Interglacial Periodsmentioning
confidence: 99%
“…During MIS 5, the vegetation was dominated by deciduous taxa, with a high percentage of Betula and Alnus pollen [50,51]. During MIS 7, the vegetation was dominated by tundra, which was mainly alder and birch [52]. [46].…”
Section: Regional Vegetation Contrasted Between Different Interglacial Periodsmentioning
confidence: 99%